Effectiveness of AI-Based Chatbots as Additional Psychiatry Assistive Technology and Alternative to Mental Health Services for Adolescents - Rahmat, Arya Dwi; Tauhid, Alfana Yudaru; Mulyadi, Faizah Azzahrah; Ellfazmy, Asyifa; Nikki Aldi Massardi; Elvira Yunita (Surabaya Physical Medicine and Rehabilitation Journal, 2026)
Background: Adolescents' lives have been profoundly impacted by the rapid development of artificial intelligence (AI), especially in mental health. AI provides easier access to learning and psychological support through chatbots. However, it also raises concerns like dependency, reduced critical thinking, risks of stress, and social isolation, especially due to social media algorithms that shape digital behavior. Data privacy and diagnostic accuracy are also key issues in mental health applications. Aim: The main objective of this review is to examine whether AI-based chatbots can serve as an additional psychiatry assistive technology to help adolescents. Scope: The review was carried out by examining research articles from databases including PubMed and Google Scholar, with a focus on papers published between 2020 and 2025. Findings: AI chatbots like Emohaa, Elomia, and SEJATI have proven effective in alleviating symptoms of depression, anxiety, and insomnia. They provide immediate support, promote emotional expression, and foster self-awareness. These chatbots have also shown promise in telerehabilitation contexts by aiding in monitoring, providing behavioral feedback, and facilitating early intervention. However, an overreliance on AI systems might hinder emotional sensitivity and social growth. Conclusion: AI chatbots hold significant promise as therapeutic resources in adolescent mental health, especially in under-resourced environments. However, their application must be carefully weighed against ethical considerations, data privacy safeguards, and continuous professional supervision. The responsible incorporation of AI into mental health care can enhance access and customization while reducing psychological and social risks.